UVMS task-priority planning framework for underwater task goal classification optimization - Gao, Yu-er; Zhang, Xiaohui; Su, Yan; Wang, Jinbao; Yang, Qihang; Bai, Wenqi; Yang, Songnan (Frontiers in Neurorobotics, 2022)
This paper presents a task prioritization strategy based on a generic underwater task goal classification transformation for multitasking underwater operational tasks: attitude control, floating manipulation, collision-free motion, especially optimizing trajectory of the end-effector of an underwater vehicle manipulator system (UVMS) in a complex marine environment. The design framework aims to divide the complex underwater operational tasks into UVMS executable generic task combinations and optimize the resource consumption during the whole task. In order to achieve the corresponding underwater task settings, the system needs to satisfy different task scheduling structures. We consider the actual application scenarios of the operational goals and prioritize and define each category of task hierarchy accordingly. Multiple tasks simultaneously enable fast adaptation to UVMS movements and planning to complete UVMS autonomous movements. Finally, an underwater vehicle manipulator system implements the task prioritization planning framework for a practical scenario with different constraints on different goals. We quickly and precisely realize the interconversion of different tasks under goal constraints. The autonomous motion planning and real-time performance of UVMS are improved to cope with the increasing operational task requirements and the complex and changing practical engineering application environments.